Relationship Between Antioxidant Capacity, Proanthocyanidin and Anthocyanin Content During Grape Maturation of Touriga Nacional and Tinta Roriz Grape Varieties - Jordão, A.M.; Correia, A.C. (South African Journal of Enology and Viticulture, 2016)
To investigate antioxidant capacity in seeds and skins during grape maturation and its relationship with anthocyanin and proanthocyanidin content, two Portuguese red grape varieties, Touriga Nacional and Tinta Roriz (Vitis vinifera L.) were studied. Two analytical methods were used for antioxidant capacity analysis: the DPPH and ABTS methods. Proanthocyanidins from seeds and skins were separated into monomers, oligomers and polymers, while 13 individual anthocyanins from the skins were also evaluated by HPLC. For both grape varieties studied, antioxidant capacity from the skins and seeds was characterised during grape maturation by a general decrease, mainly in the first weeks after véraison, followed by stabilisation and a slight increase in the values in the last three weeks of ripening. A similar tendency was observed for the amount of all the different proanthocyanidin fractions quantified. Our results also showed that seeds are an important source of proanthocyanidins with respect to the grape berry skins. Seeds were also the grape berry fraction with the highest antioxidant capacity when compared to the antioxidant capacity content of the skins. For the 13 individual monomeric anthocyanins quantified during grape maturation, evolution was generally characterised by a continuous increase in the values. However, for some of the individual anthocyanins, the continuous increase was followed by stabilisation or a decrease in the values in the last weeks of ripening. Finally, there was a positive relationship between the different proanthocyanidin fractions and antioxidant capacity of both grape varieties studied; while a negative relationship during grape maturation was obtained for individual anthocyanins.